Viability of fibroblasts in a novel probiotic storage media - KARGÜL, BETÜL; YILMAZ, MÜESSER AHU (WILEY, 2010)
A number of storage media have been investigated as to their ability to maintain the viability of the periodontal ligament (PDL) cells and thus to permit longer extra-alveolar periods prior to replantation of avulsed teeth. The aim of the present in vitro study was to evaluate the number of viable PDL cells of avulsed teeth treated by Hank's Balanced Salt Solutions (HBSS), saline, a novel probiotic solution and milk. Thirty-six freshly extracted single-rooted human teeth with closed apices were divided into one of the four experimental groups and two control groups (N = 6 each). The positive and negative controls corresponded to 0 min and an 8-h dry time respectively. Following extraction, the coronal 3 mm of PDL tissue was scraped with a #15 scalpel to remove cells that might have been damaged. The experimental teeth were dried for 30 min followed by a 45 min immersion in one of the four experimental media. Each experimental tooth, after drying and soaking, was incubated for 30 min with a 2.5 ml solution of 0.2 mg ml(-1) of collagenase CLS II and a 2.4 mg ml(-1) solution of dispase grade II in phosphate buffer saline (PBS). The cells were then labelled with 0.4% Trypan blue for determination of viability. The teeth stored in positive control demonstrated the highest number of viable PDL cells followed in rank order by HBSS, saline, Lactobacillus reuteri solution and milk. There was no significant difference in the number of viable PDL cells between HBSS, milk, L. reuteri solution and saline. Within the parameters of this study, it appears that probiotic may be able to maintain PDL cell viability as HBSS, milk, or saline.
Keywords: PERIODONTAL-LIGAMENT CELLS; SALIVARY MUTANS STREPTOCOCCI; EXTRA-ALVEOLAR PERIOD; PERMANENT INCISORS; MILK; TEETH; LACTOBACILLUS; BACTERIA; VIASPAN; TRANSPORT